Analysis of the Influence of Tourist Satisfaction and Tourist Attraction on Gunung Padang, Padang City Attractions - Gagih Pradini; Rizky Andhika Gumelar; Anisa Putri Kusumaningrum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Gunung Padang tourist destination, Padang City is one of the top tours in Padang City, West Sumatra. This research aims to find out the influence of tourist satisfaction. This method uses descriptive quantitative with an approach using primary data consisting of interviews with destination managers. Field mounts and peer questionnaires of 100 respondents, model feasibility tests, classical assumption tests and multiple linear regression tests. This research shows that the variables of the skinas of the service have a significant positive effect on the variables of tourist attractions, while tourist attractions have a significant positive effect on the variables of tourist attractions.